Marxism and literary criticism - "Eagleton, Terry" (London, 2002)
s Marx relevant any more? Why should we care what he wrote? What difference could it make to our reading of literature? Terry Eagleton, one of the foremost critics of our generation, has some answers in this wonderfully clear and readable analysis. Sharp and concise, it is, without doubt, the most important work on literary criticism that has emerged out of the tradition of Marxist philosophy and social theory since the nineteenth century.
Keywords: Marxism